Cross Clinical Reactivity among Wild Privet and Gaint Hazel Pollinosis - Siddiqui, Nadeem (Asian Journal of Pharmaceutics (AJP), 2023)
Background: Pollen from various tree and grass species is the most common cause of allergy responses around the world. Objectives: In this study, we focused on the allergenic potential and cross-reactivity between pollen extracts of Ligustrum robustum and Corylus maxima, aiming to understand the clinical significance of these interactions. Several proteins found in Ligustrum pollen have previously been identified as allergens that cause sensitization and the onset of allergic symptoms in atopic people. Our study includes the cross-reactivity between pollen extracts of L. robustum with C. maxima for clinical significance. Methods: Immunological and biochemical characterization was carried out for the purified GST compound which was assessed by sodium dodecyl sulfate polyacrylamide gel electrophoresis. The cross-reactivity studies among allergens and relevant species were evaluated by enzyme-linked immunosorbent assay inhibition assays. Results: In biochemical assays, central goods and services tax (c-GST) was not enzymatically active, whereas l-GST demonstrated high enzymatic activity. Conclusion: This research contributes to a better understanding of the allergenic properties and crossreactivity patterns between these two pollen sources. The obtained information could have implications for the development of diagnostic and therapeutic strategies for individuals with allergies.